Sperm DNA impairment in the bull: causes, influences on reproduction and evaluations - Baiee, Falah Hasan Ali; Haron, Abd Wahid; Yusoff, Rosnina; Omar, Mohamed Ariff; Degu, Nurhusien Yimer (Universiti Putra Malaysia Press, 2018)
Conventional semen examination involving sperm motility, viability and morphology remains the backbone of assessing the fertility status of a sire. However, there remains instances where these semen parameters appear normal but cases of low conception rates or failure of pregnancy occur. This review highlights the causes of sperm DNA damage and the effectiveness of techniques designed to evaluate the contribution of sperm DNA damage to lowered fertility in bulls. Among the many causes of sperm DNA impairment are imperfect spermatogenesis, faulty apoptosis, reactive oxygen species, in-vitro handling, impact of environment, radiography and the stress of cryopreservation processes. Furthermore, DNA impairment impairs fertilisation, interferes with embryonic development and implantation and blocks blastocyst formation. The most frequently used tests to determine DNA damage are the acridine orange test (AOT) using acridine orange stain with examination under a fluorescence microscope and the sperm chromatin structure assay (SCSA) using the same stain but examined with flow cytometry.